THE EFFECT OF BOWLING GAME TOWARD NUMERACY SKILLS FOR INTELLECTUAL DISABILITY STUDENT - Sari, Putri Dwi; Iriyanto, Tomas (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
Intellectual disability students experience difficulties in the learning process, especially on the material arithmeti coperation. It was caused by to the intellectual development hampered by the limitations of IQ and final stage of operational phases of the students turn from abstract to the concrete. The research design used in this study was the Single Subject Research (SSR), with ABA design models and use measuring units scores. The subjects was intellectual disability students the fifth grade in SDLB Idayu II Malang. Data collection techniques was written tests. Research revealed a effect of the use of the bowling game to increaser eduction numeracy skills as the target behavior. Advice for school and the teacher can provide methods and learning media in accordance with the needs and characteristics of students..